Penerapan hybrid working model terhadap perubahan budaya kerja dan nilai organisasi - Ainurrofiq, Ihsan; Amir, Muhammad Taufiq (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to find out how the concept of the Hybrid Working Model is used and how it affects the work culture at PT Bank DBS Indonesia as one of the companies that apply the Hybrid Working Model working arrangement. The research that will be carried out uses qualitative research methods because this study aims to understand social reality, then this study emphasizes more on meaning and seeing the values that exist in the PT Bank DBS Indonesia company. Data analysis technique with narrative analysis. The results of this study that the Hybrid Working Model that applied at PT Bank DBS Indonesia is Future of Work, Workforce, and Workplace (F3W) which provides flexibility of up to 40% of the employee's effective working hours (3 days WFO and 2 daysWFH), then there is an adjustment of the culture and values that are affected when implementing hybrid working model as evidenced by TOGETHER Movement as a support project for the PRIDE value at PT Bank DBS Indonesia. The conclusion of this study there is a positive change in the way of communicating and collaborating which becomes easier, but employees feel less enjoy and fun in their works.